Abu al-Barakat al-Baghdadi on Divine Foreknowledge and Human Free Will - Mariam Shehata (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
The present paper aims to explore the medieval philosopher Abū al-Barakāt al-Baghdādī’s (d. pre-560 AH/1164-5) position concerning the problem of divine foreknowledge and human free will and argues Abū al-Barakāt to have considered the argument for compatibility between divine foreknowledge and human free will to be invalid. One can defend either divine foreknowledge or human free will; no other solution is available. By examining his accounts on this issue through the logic and metaphysics of his book al-Muʿtabar fi-l-ḥikma, Abū al-Barakāt defense of human free will shall become evident.